(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the processes of cultural upsurge that occurred in the countries of the East, especially in Central Asia, in the 9th-12th centuries. The study examines the socio-political factors of the Eastern Renaissance, the formation of scientific centers, the development of natural and exact sciences, philosophical thought, literature, and art on the basis of a comprehensive approach. The results show that this period is a historical stage that made an incomparable contribution to the development of not only regional, but also world civilization.